The Impact of Internet Addiction on Psychological Adjustment among Students of Princess Rahma University College - Alsaideh, Jehad Ali; Abu-albasal, Nagham Mohammad; Ghnaim, Khowla A.; Alhesan, Somaia Moneeb (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims to explore the level of internet addiction among students of Special Education Department at Princess Rahma University College and to investigate the effect of this addiction on the psychological adjustment of the students. Methods: Descriptive method was used and a sample of (150) students was randomly selected. Two instruments were developed for data collection: Internet Addiction Scale and Psychological Adaptation Scale. The level of addiction was classified as low where the mean of the responses was (1-2.33), medium (2.34-3.67), and high (3.68-5). Results: The level of internet addiction among the participants was high (3.75±0.49). The average of the psychological adaptation was moderate (2.90±0.56). There was a negative relationship between internet addiction and psychological adjustment. Also, there was significant differences according to the participants’ gender in favor of female, the mean for male ((3.4±0.20)) and for female (3.9±0.56). Conclusions: Addiction to the internet has a negative impact on the psychological adjustment aspects among young people. The study recommends increasing public awareness of the risk of internet use amongst youth and establishing therapeutic counseling programs to prevent internet addiction.